Pensamento crítico em Sociologia: da variabilidade sinonímica em curso à possibilidade emancipatória - Araújo, Hermenegildo de Oliveira (2018)
The present dissertation developed for academic-political interests consists of a critical analysis about the synonymous variability verified in the theoretical-linguistic-political plane of the category Critical Thinking expressed and established in and by the current literature in the educational field. In other words, we try to think critically about the category Critical Thinking, trying to understand why this synonymous sensorial variability is practiced by teachers in the paths intrinsic to education and what are their reverberations, since this category, even subscribed in the dynamic and ideological course to the sociometabolic logic of capital, is a latent power of societal alternation, but it transits into a distinct temporality and specificity in the absence of the interests of historical subjects as indicators for this societal alternation, and which freely ambition to associate. In fact, this category as observed is not aligned with the critical thinking that denies and breaks with the (re) production of the logic of capital, since it is manipulated as a commodity. Therefore, we have seen through this critical analysis (theoretical research) to establish, in a preliminary way, under the relentless historical condition of the object, since only Man can confer theoretical ballast establishing material markings and meanings, which Critical Thinking, as a sociological category of the analysis of historical-concrete conditions, claimed by historical subjects inserted in the spheres of knowledge (public basic education), is treated by its "users" as commodity and this is subsumed to the historical logic of capital, therefore inherent in its own crisis, which is global, contradictory and modern.